Investigation On Conventional Braking With High Speed Performance Electromagnetic Braking System - Dr.K.G.Saravanan, S.Pradeep (International Journal of Advanced Science and Technology, 2020)
The braking is the action of making a moving vehicle to stop or slow down by applying the brake. According to our day to day life there are many advance technology in the braking system are used to be developed in the mechanical field. the electromagnetic braking concept are one of the latest developing technology focused by many companies to overcome the problem faced in the conventional braking system and they believe that the electromagnetic braking system reduce the braking distance compare to the conventional braking system. In the conventional braking process the movement of vehicle slowdown or stop by using frictional force. The friction between two surface pressures together to convert kinetic energy to heat energy by this energy conversion the vehicle movement is used to be stop. In the electromagnetic braking system we used magnetic field to stop the movement of the vehicle, hence the friction is very less compare to the conventional braking system. The electromagnet are made by the current carrying coil which is winded over the iron core. When the current is used to pass over the coil it produce magnetic field by this concept the electromagnetic braking is used to be function. The speed of the braking is high because of the movement of the electron, as per the research the electron speed is less than one percent of light speed. Due to this property the electromagnetic braking are used to produce high braking torque in short interval of time. The most common problem in the conventional braking system is high generation of heat and produce high wear and tear .in the electromagnetic braking system the braking is done by frictionless concept, hence there is no heat generation and high wear and tear production. In this project we combined the electromagnetic braking and conventional braking to make a result of high performance braking system. the project explain that the conventional braking system are work for particular speed limit of the vehicle, when the vehicle reached above the speed limit the electromagnetic braking system is used to combine with conventional braking system to stop the movement of the vehicle and to reduce the braking distance. We use speed sensor and control system to monitor the movement of the vehicle and the braking system. Moreover we used the electromagnetic braking concept as high speed performance braking not as the emergency braking.